Young Europeans and their emerging ideas about political identities in an age of authoritarian dissent and fabricated news: what can we do to encourage their political understanding? - Ross, Alistair (Alliance for Childhood European Network, 2022)
This research project focuses on young European’s political identities and the values that they express, and the implications this may have for political education. The qualitative study used 324 small discussion groups with groups of 11 to 19 year-old, across 29 European countries. The processes of deliberative discussions let the participants feel in control of the discussion and use their own terms and expressions. Discussions contrasted their views with those they felt were held by others, such as older people, those in other parts of their country, and those in other countries: contrasts and comparisons led to more refined and nuanced expressions. Analysis suggests that there have been significant changes in political structures in Europe, in the demography of the country (particularly increased diversity), and in the technology of the internet, that distinguish the views of this cohort of young people. The study also suggests that the research methodology might be the basis for supporting young people’s learning and development in this area.